Adaptedness and Temperament of Students - A S Verozub (Peoples' Friendship University of Russia (RUDN University), 2012)
In the article the results of the research of the temperament of students with various degrees of adaptedness are presented, the peculiarities and psychological structure of temperament in more and less adapted first-year students are described in particular.